2022
DOI: 10.1002/cnma.202100428
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Carbon‐Supported Cobalt Nitride Nano‐Catalyst

Abstract: Transition metal nitrides have attracted great interest among the non‐noble catalysts employed in heterogeneous catalytic processes because of their exceptional stability and catalytic potential. However, the approach for their synthesis has remained a tremendous challenge. This study presents the synthesis of Co4N/C catalyst fabricated at 400, 600, and 800 °, symbolized as Co4N/C‐400, Co4N/C‐600, Co4N/C‐800, respectively. The characterization of fabricated catalysts is carried out through various advanced ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…In Figure 2c, all the samples show a peak at 26°, which can be attributed to the (002) plane of graphitic carbon (PDF#75‐0444) [22] . In Figure S5, for Co 4 N/Co, the diffraction maxima at 35.5°, 44°, 52°, and 76° match well with the cubic phase of Co 4 N with the space group Pm3 m (ICDD 04–021‐6262), [10] indicating its presence in the sample. However, the peaks at 44°, 52° and 76° are slightly shifted compared to Co 4 N and are between the main peaks of cubic cobalt and Co 4 N, indicating that Co 4 N and Co can be present at the same time.…”
Section: Resultsmentioning
confidence: 79%
“…In Figure 2c, all the samples show a peak at 26°, which can be attributed to the (002) plane of graphitic carbon (PDF#75‐0444) [22] . In Figure S5, for Co 4 N/Co, the diffraction maxima at 35.5°, 44°, 52°, and 76° match well with the cubic phase of Co 4 N with the space group Pm3 m (ICDD 04–021‐6262), [10] indicating its presence in the sample. However, the peaks at 44°, 52° and 76° are slightly shifted compared to Co 4 N and are between the main peaks of cubic cobalt and Co 4 N, indicating that Co 4 N and Co can be present at the same time.…”
Section: Resultsmentioning
confidence: 79%
“…34,35 In the Fourier transform infrared (FT-IR) spectra of Co-L1(1:4.5)@C-800, the characteristic Co−N x stretching bands were observed at 558 cm −1 , which is in accordance with the reported literature value. 37 Further, the TEM study revealed that the Co-L1(1:4.5)@C-800 material consisted of an average particle size of 12.54 nm (ranging from 4 to 24 nm; Figure 1g,h). The high-resolution TEM image exhibited a wellresolved lattice spacing of 0.204 nm corresponding to the Co(111) plane (Figure 1i).…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…In the deconvoluted nitrogen N 1s XPS spectra, three peaks were observed, which indicated the presence of pyridinic-type (398.2 eV), pyrrolic-type or Co–N x (399.1 eV), and graphitic-type (401.2 eV) nitrogen in the material (Figure d) . In the deconvoluted O 1s spectrum, three peaks centered at 531.5 eV (CO), 532.8 eV (–C–O), and 535.2 eV (–OH or H 2 O) (Figure e) were observed. , In the Fourier transform infrared (FT-IR) spectra of Co-L1(1:4.5)@C-800, the characteristic Co–N x stretching bands were observed at 558 cm –1 , which is in accordance with the reported literature value . Further, the TEM study revealed that the Co-L1(1:4.5)@C-800 material consisted of an average particle size of 12.54 nm (ranging from 4 to 24 nm; Figure g,h).…”
Section: Resultsmentioning
confidence: 96%
“…Several photoactive materials are famous for photocatalysis application of degradation of the organic pollutants. The catalytic membranes have also shown promising potential to degrade or convert the organic contamination to valuable products [250,251] …”
Section: Self‐cleaning and Self‐repairing Membranes For Oil/water Emu...mentioning
confidence: 99%
“…The catalytic membranes have also shown promising potential to degrade or convert the organic contamination to valuable products. [250,251] Figure 25. Cross-section and outer surface SEM images of the membranes sintered at 1350 °C and produced with pure and mixed SiC and Si powders as starting ceramic materials:, and Visual aspect and microscopic photographs of the water/oil emulsion before and after the filtrations through the HF-SiC70Si30 membrane.…”
Section: Self-cleaning and Self-repairing Membranes For Oil/water Emu...mentioning
confidence: 99%